New ferroelectric and antiferroelectric liquid crystals studied by complementary methods. Issue 3 (19th February 2017) - Fitas, Jakub; Dłubacz, Anna; Fryń, Patryk; Marzec, Monika; Jaworska-Gołąb, Teresa; Deptuch, Aleksandra; Kurp, Katarzyna; Tykarska, Marzena; Żurowska, Magdalena
ABSTRACT: Four new synthesised liquid crystalline compounds belonging to the homologous series of fluorinated biphenyl benzoate esters have been studied to compare their dielectric and electrooptic properties. Three of the studied compounds exhibited ferro- and antiferroelectric phases while one of them exhibited only one liquid crystalline phase – ferroelectric SmC*. No paraelectric phase was detected and straight transition between isotropic liquid and ferroelectric phases was observed for all studied compounds. Tilt angle for all of the studied compounds was equal to ca. 45ᵒ in the liquid crystalline phases, except temperature range close to the isotropic liquid–ferroelectric smectic phase transition. Temperature dependences of helical pitch, spontaneous polarisation and switching time have been determined. Based on XRD results, temperature dependence of the layer thickness has also been found. Only one relaxation process has been revealed in the ferroelectric as well as antiferroelectric phases, even the bias field up to 8 V/µm was applied. The dielectric and electrooptic data are discussed based on the mean-field theory predictions. GRAPHICAL ABSTRACT: